Cover Feature: An Enzyme‐Mediated Amplification Strategy Enables Detection of β‐Lactamase Activity Directly in Unprocessed Clinical Samples for Phenotypic Detection of β‐Lactam Resistance (ChemBioChem 20/2018). (4th October 2018) - deBoer, Tara R.; Tarlton, Nicole J.; Yamaji, Reina; Adams‐Sapper, Sheila; Wu, Tiffany Z.; Maity, Santanu; Vesgesna, Giri K.; Sadlowski, Corinne M.; DePaola, Peter; Riley, Lee W.; Murthy, Niren
Abstract : The cover feature picture shows a pictorial representation of the enzyme‐empowered amplification technology, DETECT. This amplification strategy was applied to enhance the detection of the antibiotic resistance‐conferring enzyme, β‐lactamase, and increased the limit of detection by 40 000 times relative to the standard comparable detection method. This enzyme‐powered amplification strategy enabled the detection of β‐lactamase activity directly in unprocessed clinical urine samples that contained antibiotic‐resistant bacteria that cause urinary tract infection. DETECT has the potential to make evidence‐based treatment practices at the time of care routinely possible. More information can be found in the communication by T. R. deBoer, L. W. Riley, N. Murthy, et al. onpage 2173 in Issue 20, 2018 (DOI:10.1002/cbic.201800443 ).